The effect of COVID-19 on U.S. pork exports to East Asia - Stutrud, Morgan Steele (Kansas State University, 2022)
The motivation for this research was brought on by the COVID-19 pandemic and the supply chain disruptions it caused when the virus spread worldwide, infecting employees in manufacturing positions, causing production to slow. This was especially observed in the pork and pork products industry. As employees at processing plants fell ill, production decreased and, in some cases, halted entirely. This caused a shortage of pork products both domestically and destined to be exported. The research question is: What effect did the COVID- 19 pandemic have on U.S. exports to the four major East Asian destinations? The overall objective of this study is to determine the extent of COVID-19’s effect on U.S. pork exports to East Asia. Over the years, pork exports and profits have consistently increased. The sector earned a record $8.1 billion in revenue in 2021, which was a 5% increase from 2020. In 2021, China, Japan, and Mexico imported approximately $1.7 billion of U.S. pork, accounting for 63% of U.S. pork exports. Due to China and Japan being the top two international destinations for U.S. pork, and East Asia accounting for half of all U.S. pork exports by volume, this region will be the focus of how COVID-19 affected U.S. pork exports. The close contact of livestock processing led to rapid spread of the virus through these facilities. It was reported that between April and May 2020, 17,358 workers were diagnosed with COVID-19 at 264 processing plants in 28 states, and 91 workers died, slowing the production of pork products, and limiting the quantity available for export. Data for this research were collected primarily from the USDA’s Economic Research Service (ERS) and Foreign Agricultural Service (FAS) GATS (Global Agricultural Trade System). The impact of COVID-19 was assessed by running a regression using the software program, Stata™. The study used monthly data from January 2011 through June 2022. It focused on pork and pork products in the consumer-oriented section of the database using both quantity and value of exports to the four focus countries – China, Japan, South Korea, and Taiwan. Prior to COVID-19, U.S. pork exports were estimated to be 194,443 MT/month, while the amount exported during the COVID-19 era was 237,086 MT/month. In the COVID-19 era, the average export of U.S. pork was higher than in the previous era. This was true for East Asia as a whole and for China. However, the remaining countries saw a reduction in U.S. pork exports during the COVID-19 period. The impact of the COVID-19 virus did not have a statistically significant impact South Korea. However, it did have a statistically significant impact on China, Japan, and Taiwan. Therefore, the hypothesis that there was no COVID-19 effect on U.S. pork and pork product exports was rejected in three of the four cases. These results provide insight into the relationships between U.S. pork and pork product exports to the four East Asian countries and their imputed prices. Members of the pork industry and policymakers will be able to better prepare for future opportunities in pork export by understanding the growth in demand and the disruptions that a major global event might cause.
Keywords: COVID-19 pandemic; U.S. pork exports; China